Stenotrophomonas Maltophilia Pneumonia in a COPD Patient with Left Atrial Myxoma: A Case of Rare Clinical Presentation - Ronak Prakashkumar Shah; Parth Rohitkumar Shah (Journal of Clinical and Diagnostic Research)
Stenotrophomonas maltophilia (S.maltophilia) is an emerging multidrug-resistant pathogen, often implicated in respiratory infections in patients with chronic lung disease. The present case report presents a unique association between S. maltophilia pneumonia and an incidental left atrial myxoma, contributing to respiratory distress. Hereby, the authors present a case report of a 52-year-old male with Chronic Obstructive Pulmonary Disease (COPD) presented with bilateral lower limb oedema, progressive dyspnoea, productive cough, and intermittent fever for 15 days. Upon admission, he exhibited tachycardia, tachypnoea, and hypoxaemia (SpO2 88% on room air). Chest examination revealed bilateral wheezing and crackles. Investigations showed leukocytosis, elevated inflammatory markers, and an abnormal chest X-ray with fibrotic changes and minimal pleural effusion. Echocardiography identified a 3.5 cm left atrial myxoma prolapsing into the mitral valve, along with severe pulmonary hypertension. Contrast-enhanced CT (CECT) confirmed the myxoma and revealed emphysematous and pneumonic changes. The patient was initially managed as a case of acute community-acquired pneumonia with acute decompensated heart failure using broad-spectrum antibiotics, bronchodilators, steroids, and diuretics. Due to respiratory distress and type 2 respiratory failure, Bilevel Positive Airway Pressure (BIPAP) support was initiated. Sputum culture identified S. maltophilia, which was sensitive to Trimethoprim-Sulfamethoxazole (TMP-SMX), leading to a targeted antibiotic regimen. The patient showed significant clinical improvement, allowing for weaning from BIPAP and oxygen support. Once stabilised, he was referred for surgical resection of the left atrial myxoma. The present case emphasises the importance of early recognition and targeted treatment of S. maltophilia pneumonia in COPD patients. Additionally, it highlights the role of comprehensive cardiovascular assessment in patients with persistent respiratory symptoms.